Women's Leadership and Effective Communication: The Key to Improving Employee Work Motivation at BPR Jakarta - Nataleo, Sally; Susilo, Daniel (Riviera Publishing, 2025)
This study aims to analyze the influence of female leadership and effective communication on employee work motivation at BPR in Jakarta. The method used is a quantitative approach with SmartPLS analysis technique, and involved 120 respondents as samples. The results showed that female leadership and effective communication have a significant effect on work motivation. Women's leadership style that prioritizes empathy, collaboration, and participation is able to create a supportive work environment and encourage employee morale. Meanwhile, effective communication increases motivation through clarity of information and positive interpersonal relationships. These findings are in line with feminist organizational communication theory that emphasizes the importance of relational, inclusive, and participatory approaches in building a productive work culture. This research suggests the importance of strengthening women's roles in leadership and building open communication to increase work motivation.